Pengaruh Rasio Keuangan terhadap Perubahan Laba Perusahaan Batubara dan Migas yang terdaftar di BEI - Mukti, Alwi; Saleh, Suji Abdullah; Aprilliawati, Yeti; Suwondo, Sulistia (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
This study aims to determine the effect of Current Ratio, Quick Ratio, Debt to Assets Ratio, Debt to Equity Ratio, Inventory Turn Over, Fixed Assets Turn Over, Total Assets Turn Over, and commodities on profit changes in coal, oil and gas companies listed on IDX. The data obtained in this study used the documentary method and the online data tracking method. The results of multiple linear regression analysis show that the variables Current Ratio, Quick Ratio, Debt to Equity Ratio, and Total Assets Turn Over have a positive effect on earnings changes. While the variable Debt to Asset Ratio, Inventory Turn Over, Fixed Assets Turn Over, and commodities do not have a positive effect on changes in profit. Simultaneous testing shows the Current Ratio, Quick Ratio, Debt to Assets Ratio, Debt to Equity Ratio, Inventory Turn Over, Fixed Assets Turn Over, Total Assets Turn Over, and commodities have an influence on profit changes with a predictive ability of 50.4%.